2017
DOI: 10.1038/srep45049
|View full text |Cite
|
Sign up to set email alerts
|

Global identification and analysis of isozyme-specific possible substrates crosslinked by transglutaminases using substrate peptides in mouse liver fibrosis

Abstract: The transglutaminase (TG) family comprises eight isozymes that form the isopeptide bonds between glutamine and lysine residues and contribute to the fibrotic diseases via crosslinking-mediated stabilization of ECM and the activation of TGF-β in several tissues. However, despite a growing body of evidence implicating TG2 as a key enzyme in fibrosis, the causative role of TG2 and the involvement of the other isozymes have not yet been fully elucidated. Therefore, here we clarified the distributions of TG isozyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Transglutaminases (TGs) are Ca(2+)-dependent enzymes that catalyze the formation of covalent bonds between glutamine and lysine residues, and contribute to fibrotic diseases via crosslinking-mediated stabilization of extracellular matrix (Eckert et al, 2014; Iismaa et al, 2009; Lorand and Graham, 2003). TGM1 , TGM3 and TGM5 have been associated with mouse liver fibrosis and altered healing processes (De Koning et al, 2012; Tatsukawa et al, 2017), which is interesting since NAFLD can progress to cirrhosis. According to the tissue-specific pattern of mRNA expression profiles from 79 human tissues and cell types (http://biogps.org), TGM5 is highly expressed in the liver, although the precise role of TGM5 in NAFLD is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Transglutaminases (TGs) are Ca(2+)-dependent enzymes that catalyze the formation of covalent bonds between glutamine and lysine residues, and contribute to fibrotic diseases via crosslinking-mediated stabilization of extracellular matrix (Eckert et al, 2014; Iismaa et al, 2009; Lorand and Graham, 2003). TGM1 , TGM3 and TGM5 have been associated with mouse liver fibrosis and altered healing processes (De Koning et al, 2012; Tatsukawa et al, 2017), which is interesting since NAFLD can progress to cirrhosis. According to the tissue-specific pattern of mRNA expression profiles from 79 human tissues and cell types (http://biogps.org), TGM5 is highly expressed in the liver, although the precise role of TGM5 in NAFLD is not known.…”
Section: Discussionmentioning
confidence: 99%
“…TG was linked with liver fibrosis in 2001 (73) using an e-(g-glutamyl) Lys crosslink antibody that has since been reported to be nonspecific (74). TG isozyme-specific substrates have demonstrated an increase in the activities of intracellular TG1 and of extracellular TG2 during liver fibrosis (75), implicating TG2 in ECM crosslinking. Effective reduction of liver fibrosis has been reported using competitive inhibitors of TG (76), such as cystamine (a nonspecific enzyme inhibitor that interferes with sulfhydryl enzymes), and without using a proper (e.g., tertiary ammonium) control.…”
Section: Ongoing Researchmentioning
confidence: 99%
“…Effective reduction of liver fibrosis has been reported using competitive inhibitors of TG (76), such as cystamine (a nonspecific enzyme inhibitor that interferes with sulfhydryl enzymes), and without using a proper (e.g., tertiary ammonium) control. However, 2 independent groups have shown that TG2 knockout mice are not altered in collagen crosslinking or liver fibrosis (75). Again, a comparison of TG isozyme-specific activities before and after induction of liver fibrosis in TG2 knockout mice has not been reported, so it is not clear if there are disease-related compensatory changes in TG isozymes in the ECM in response to TG2 deletion or if liver fibrosis is TG independent.…”
Section: Ongoing Researchmentioning
confidence: 99%
“…These peptides have been widely used as tools to efficiently visualize enzyme activity in several tissues including skin epidermis . Moreover, possible substrates have been identified in feasible and efficient procedures .…”
Section: Introductionmentioning
confidence: 99%